2000
DOI: 10.1007/s001670050004
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of knee hyperextension and of the impingement of the anterior cruciate ligament: a cinematographic MRI study with impact on tibial tunnel positioning in anterior cruciate ligament reconstruction

Abstract: This study analyzed the interaction between the anterior cruciate ligament (ACL) and the intercondylar notch roof (INR) in hyperextension of the knee using magnetic resonance cinematography. Cinematographic image series of 15 knees were investigated. Two independent observers identified the image that displayed the beginning of contact between the ACL and the INR. They determined knee extension on this image and on the image that displayed maximum hyperextension of the knee. Correlations between a variable rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 26 publications
0
51
3
2
Order By: Relevance
“…One of the most serious concerns after ACL reconstruction is impingement of the graft against the intercondylar roof [6,[11][12][13][16][17][18]. To avoid this, many surgeons place the tibial tunnel in the posterior part of the ACL insertion site (PL insertion site) [4,14,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most serious concerns after ACL reconstruction is impingement of the graft against the intercondylar roof [6,[11][12][13][16][17][18]. To avoid this, many surgeons place the tibial tunnel in the posterior part of the ACL insertion site (PL insertion site) [4,14,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Following Julliard's philosophy, the software is used to optimize 2 criteria: identification of a minimal anisometry profile that is favorable (graft loosening in flexion) in the anatomical area of ACL insertion 26 and prevention of any conflict between the graft and the femoral notch. 13,14,17,18 Surgical Technique A standard surgical protocol was followed for both conventional and navigated procedures. All procedures were performed with the patient under general anesthesia and supine, and a tourniquet was placed above the knee.…”
Section: Acl Logics Julliard Protocol: Methods and Philosophy Of Usementioning
confidence: 99%
“…There is an extensive debate on notch impingement in the literature, which is beyond the scope of this discussion, but we consider in this study that it must be avoided to prevent postoperative rupture of the graft in full extension. [16][17][18] It was interesting to note when looking at the tibial tunnels that the value CTT/STD (which characterizes the anterior positioning of the tibial tunnel with respect to the most anterior and posterior points of the tibial plateau measured on sagittal radiographs) was lower in the navigated group (31.4; range, 18.2-40) than in the conventional group (34.4; range, 22.2-43.4). Therefore, although the positioning was globally more anterior in the navigated group, the risk of notch impingement has been reduced.…”
mentioning
confidence: 97%
“…In addition, there can be increased impingement of the reconstructed graft against the intercondylar roof in knees with excessive hyperextension, which in turn results in graft deterioration or re-rupture. Jagodzinski et al,66) in a cinematographic magnetic resonance imaging study, reported that impingement between the ACL and the intercondylar roof occurred at 6.3° hyperextension. They emphasized the importance of posterior placement of the tibial tunnel to avoid impingement in knees with increased hyperextension.…”
Section: Reconstruction Options and Graft Selectionmentioning
confidence: 99%